Late events after anti-CD19 CAR T-cell therapy for relapsed/refractory B-cell non-Hodgkin lymphoma - Cordeiro, Ana Costa; Durisek, George; Batista, Marjorie Vieira; Schmidt, Jayr; de Lima, Marcos; Bezerra, Evandro (Frontiers in Oncology, 2024)
Background The short-term complications from chimeric antigen receptor T-cell therapy (CART) are well characterized, but the long-term complications still need to be further investigated. Therefore, herein, we will review the currently available literature published on the late adverse events following CART. Methods We reviewed published data available from pivotal trials and real-world experiences with anti-CD19 CART (CART19) for adults with lymphoma. We defined late events as occurring or persisting beyond 1 month after CART infusion. We focused our literature review on the following late-event outcomes post-CART19: cytopenia, immune reconstitution, infections, and subsequent malignancies. Results Grade 3–4 cytopenia beyond 30 days occurs in 30%–40% of patients and beyond 90 days in 3%–22% of patients and is usually managed with growth-factor and transfusion support, along with neutropenic prophylaxis. B-cell aplasia and hypogammaglobulinemia are expected on-target off-tumor effects of CART19, 44%–53% of patients have IgG < 400 mg/dL, and approximately 27%–38% of patients receive intravenous immunoglobulin (IVIG) replacement. Infections beyond the initial month from CART19 are not frequent and rarely severe, but they are more prevalent and severe when patients receive subsequent therapies post-CART19 for their underlying disease. Late neurotoxicity and neurocognitive impairment are uncommon, and other causes should be considered. T-cell lymphoma (TCL) after CART is an extremely rare event and not necessarily related to CAR transgene. Myeloid neoplasm is not rare post-CART, but unclear causality given heavily pretreated patient population is already at risk for therapy-related myeloid neoplasm. Conclusion CART19 is associated with clinically significant long-term effects such as prolonged cytopenia, hypogammaglobulinemia, and infections that warrant clinical surveillance, but they are mostly manageable with a low risk of non-relapse mortality. The risk of subsequent malignancies post-CART19 seems low, and the relationship with CART19 and/or prior therapies is unclear; but regardless of the possible causality, this should not impact the current benefit–risk ratio of CART19 for relapsed/refractory B-cell non-Hodgkin lymphoma (NHL).